INSIDENSI PENYAKIT AKAR GADA (Plasmodiophora brassicae Wor.) PADA TANAMAN KUBIS DI DESA RURUKAN DAN KUMELEMBUAY KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Frida Towaki; Max M. Ratulangi; Guntur S.J. Manengkey; Henny V.G. Makal (Universitas Sam Ratulangi, 2014)
ABSTRACTFrida Towaki. Incidence of Clubroot Disease (Plasmodiophora brassicae Wor.) Cabbage Plants in the Village of Rurukan and Kumelembuay East Tomohon District Tomohon City. Guidence Ir. Max M. Ratulangi, MS as chairman, Ir. Guntur S.J. Manengkey, MP and Ir. Henny V.G. Makal, M.Si as memberThe study aimed to determine the incidence of root diseases clubroot on cabbage in the village Rurukan and Kumelembuay, Eastern District of Tomohon, Tomohon . This research was conducted in the village of Rurukan and Kumelembuay sub district East Tomohon, Tomohon city, and continued in the laboratory for microscopic observation of the pathogen Plasmodiophora brassicae. Data retrieval clubroot disease incidence for each village determined four blocks, each block of the extent of 0.5 ha and made sliced diagonally to get five plots with a size of 2.5 x 2.5 m, spacing is 50 x 40 cm so that each plot 32 and the number of plants from the plots do root disease incidence data retrieval clubroot. Data collection was started at the age of 21 plants DAP, with an interval of one week observation period. The result showed that the cabbage plant in the village Kumelembuay and Rurukan Plasmodiophora brassicae Wor already infected. Clubroot cause of the disease with the symptoms experienced withered plant leaves and roots when plants revoked visible swelling. The level of pathogen attack in the village of Rurukan average was 52.17 % and 46.40 % in the Village Kumelembuay.Keywords : Plasmodiophora brassicae Wor, Cabbage